Branched Polymer Materials as Proton Exchange Membranes for Fuel Cell Applications. (27th April 2022) - Neelakandan, Sivasubramaniyan; Wang, Li; Zhang, Boping; Ni, Jiangpeng; Hu, Meishao; Gao, Chunmei; Wong, Wai-Yeung; Wang, Lei
Abstract: Recent progress on branched polymer membranes as electrolyte materials for proton exchange membrane fuel cell (PEMFC) applications has attracted interest due to the limitations of commercially available Nafion® membranes. Branched polymer membranes have shown improved chemical stability, proton conductivity, and good solubility. The branching degree and the structure of the branching agent have an essential correlation with the characteristics of the polymer membranes. This review presents the most recent and promising design strategies and characteristics of branched polymers as proton exchange membranes for both low- and high-temperature proton exchange membrane fuel cells. Recent advances in branched polymers are summarized, including branched sulfonated poly(aryl ether)s, branched sulfonated polyimides, branched polybenzimidazoles, etc. The remaining challenges and prospects in proton exchange membranes are also discussed.